The Paradox of AI Integration in Basic Science Project-Based Learning: Comparing Perceived Effectiveness and Actual Product Quality - Sutri Novika; Rofiqoh Hasan Harahap; khairiah; Lia Afriyanti Nasution; Muhammad Zafar Tholib (Jurnal Penelitian Pendidikan IPA, 2026)
This study investigates the impact of Artificial Intelligence (AI) integration in Project-Based Learning (PjBL) within a Basic Science Concepts course, specifically focusing on the paradox between student perceptions and actual learning performance. A quantitative comparative design was employed, involving pre-service teachers divided into AI-reliant and non-AI groups. Data were collected through Likert-scale questionnaires and project product assessment rubrics, then analyzed using the Mann–Whitney U test. The results reveal a significant disparity: while the AI group reported significantly higher perceptions of learning effectiveness and teamwork satisfaction, their actual product quality and conceptual depth in science were lower than those of the non-AI group. This suggests that AI integration may create an illusion of competence, where ease of information access reduces the depth of critical inquiry and collaborative synthesis. The study concludes that AI should function as a guided cognitive tool rather than a primary source in science education. These findings offer critical implications for educators to design AI-integrated PjBL that prioritizes conceptual understanding over technological convenience.